Relationships Between Health Beliefs, Fear of COVID-19, Knowledge of HIV Transmission, And HIV Preventive Behaviors Among Young Thai Men Who Have Sex with Men During the COVID-19 Pandemic - Anongluk Vongtree; Natawan Khumsaen; Samrej Tienthong; Supannee Peawnalaw; Panarat Chenchob (Medsci Publications, 2024)
Background: Young Thai men who have sex with men (MSM) are at high risk of HIV transmission, making effective prevention crucial. This study aimed to examine the relationships between health beliefs, fear of COVID-19, knowledge of HIV transmission, and HIV preventive behaviors among young Thai MSM during the COVID-19 pandemic. Methodology: A cross-sectional online questionnaire study guided by the health belief model was conducted among young Thai MSM using snowball sampling. Data on HIV/AIDS health beliefs, knowledge of HIV prevention, fear of COVID-19, and HIV preventive behaviors were collected and analyzed using descriptive and inferential statistics. Results: The study included 134 participants (59.7% gay, 40.3% transgender). Knowledge of HIV prevention, fear of COVID-19, and HIV preventive behaviors were at a moderate level. Perceived severity of HIV/AIDS, perceived benefits of HIV prevention, self-efficacy for HIV prevention, knowledge of HIV transmission, and fear of COVID-19 were significantly related to HIV preventive behaviors among young Thai MSM (p<.05). These five variables were predictors of HIV preventive behaviors (Adjusted R2 = 0.304, F=6.740, p<0.05). Conclusions: The findings highlight the need for intervention programs focused on improving health beliefs and promoting HIV preventive behaviors among young Thai MSM.